Multimodality approach to the diagnosis and management of constrictive pericarditis. Issue 4 (2nd April 2020) - Ansari‐Gilani, Kianoush; Gilkeson, Robert C.; Kikano, Elias G.; Hoit, Brian D.
Abstract: Despite advances in cardiovascular imaging, the diagnosis of constrictive pericarditis remains challenging. A multimodality approach to the diagnosis of CP is essential to (a) fully assess the extent of pericardial thickening and calcification, (b) detect the functional and hemodynamic consequences of the constricting pericardium, and (c) implement the optimal management strategy in these often complex cases. This case‐based review highlights the role and diagnostic ambiguities of multimodality imaging.